coastDat-2 COSMO-CLM Atmospheric Reconstruction ... - Geyer, Beate; Rockel, Burkhardt (World Data Center for Climate (WDCC) at DKRZ, 2013)
Project: coastDat-2 - CoastDat-2 (http://www.coastdat.de/about_us/index.php) comprises a compilation of coastal analyses (that is hindcasts and reconstructions) and scenarios for the future obtained from numerical models. The atmospheric part of the dataset is simulatated using the COSMO-CLM (http://www.clm-community.eu). The objective is to provide a consistent meteo-marine data set. Summary: This is an atmospheric hourly hindcast for Western Europe and the North Atlantic using COSMO-CLM version 4.8_clm_11 with spectral nudging from 1948-2012. The model uses a rotated grid with 254 x 248 grid points and a grid point distance of 0.22 degrees, the rotated North pole is located at 170 W, 35 N. In rotated coordinates the model area extends from 30.44 W to 25.22 E, 25.72 S to 28.62 N, in geographical coordinates this corresponds to about 68 W to 82 E, 25.6 N to 81.4 N. ...